Nigeria: A Study of Abdullahi Abubakar’s Citizens or Strangers? - Issa, Aisha; Hanafi Monsur, Alabere (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Political and economic factors such as rivalry, intolerance, land ownership, power tussle, and so on are often the major causes of conflicts in every human society. As a peculiar social phenomenon, virtually every society in the world has witnessed one form of conflict or the other. Situated between causes and effects, it takes different shapes and dimensions from society to society. The usual atmospheres are inter-racial conflict, inter-tribal/ethnic conflict, inter-state conflict, inter-political conflict, etc. In Nigeria, especially the north central zone of the country, the conflictual incidents cum associated fatalities between the pastoralists and sedentary farming communities has risen high and taken appalling dimensions in the recent time. In dealing with such phenomenon, irrespective of its nature, studies in issues in conflict and conflict resolution have revealed that analysing the dynamics of a specific conflict, among others, is a vital step towards its resolution. To this end, therefore, theoretically situated between social functionality of literature and conflict analysis and resolution, the paper examines Abdullahi Abubakar’s play, Citizens or Strangers? as a theatrical approach towards analysing the dynamics of the farmer-herdsmen crisis in Nigeria, thereby providing an in-depth understanding of it and suggesting a lasting resolution.